Implementasi Program Beasiswa Pendidikan Berkualitas Dan Gratis (Perintis) Bagi Mahasiswa di Kabupaten Lamongan Tahun (2022-2023) - M.Aditiya Azrul P; Yendra Erison; Imam Fadlli; Mugito; Bambang Amir Alhakim (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2024)
The aim of this research is to achieve successful implementation of the quality and free scholarship program (PERINTIS) for students in Lamongan Regency who are less prosperous and high achieving students organized by the Regent of Lamongan through the Lamongan Regency Education Office. The type of research used is qualitative with a descriptive approach, namely by describing and analyzing research results. So it can be accounted for and easily understood. This research uses data sources from scientific journals, literature books, official websites. This research also uses data collection techniques by observation, interviews and documentation. The informant selection technique uses purposive sampling and the data sources used are primary data and secondary data. The research results show that the implementation of the PERINTIS scholarship program can be said to be in accordance with the criteria of Edward III's theory, namely, communication, resources, disposition and bureaucratic structure. So the results obtained were that the implementation of the PERINTIS scholarship program carried out by the Lamongan Regency Education Office was quite effective. The implementation of this program is beneficial for the community and organizations and the quality and free scholarship program (PERINTIS) will be carried out on an ongoing basis. There are several obstacles in implementing the PERINTIS scholarship program, including selection time constraints in determining whether recipients of the PERINTIS scholarship program are eligible or not, as well as limited numbers and time for the survey team.